2014
DOI: 10.21660/2014.14.140601
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Silt Content on the Anisotropic Behaviour of Silt-Sand Mixtures

Abstract: ABSTRACT:The anisotropy of sand has not been fully studied in terms of the effects of different silt content. This study investigates the effects on anisotropy in Tehran sand with various silt contents. The tests performed in this research include some Hollow Cylinder Torsion Shear Tests conducted on 400kPa confining stresses. The samples had 0, 15, 30, and 50 percent silt contents, and the effect of the inclination angle on the major principal stress "α" was investigated with a particular emphasis on silt con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
(29 reference statements)
0
2
0
Order By: Relevance
“…The modulus reduction and damping curves can be fit with other soil models including Vucetic-Dobry, and Hyperbolic [11,12]. These data are still in a relatively low strain range when compared to other TOSS data [13,14]. A full discussion of models, data fitting, and application to site response analysis or other geotechnical models such as t-z curves are beyond the scope of this paper.…”
Section: Fig6 G From Be Tests Under Different σ1 and σ3mentioning
confidence: 99%
“…The modulus reduction and damping curves can be fit with other soil models including Vucetic-Dobry, and Hyperbolic [11,12]. These data are still in a relatively low strain range when compared to other TOSS data [13,14]. A full discussion of models, data fitting, and application to site response analysis or other geotechnical models such as t-z curves are beyond the scope of this paper.…”
Section: Fig6 G From Be Tests Under Different σ1 and σ3mentioning
confidence: 99%
“…Rabbi et al [33] defined undrained instability based on the steady behavior observed on the instability line. Different authors have analyzed the influence of fines content on the onset of undrained instability and on the position of the instability line [34][35][36][37][38][39][40][41]. Additionally, [42][43][44][45] studied the effect of sample preparation on the locus of the onset of undrained instability.…”
Section: Introductionmentioning
confidence: 99%